2020
DOI: 10.21203/rs.3.rs-23189/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PM2.5 exposure induced renal injury via the activation of the autophagic pathway in the rat and HK-2 cell

Abstract: Abstract Background: Exposure to airborne fine particulate matter (PM2.5) has been declared to be harmful to human kidney. However, whether activation of the autophagic pathway plays key roles in the nephrotoxicity caused by PM2.5 exposure is still poorly understood. The aim of this study was to explore the mechanism of kidney damage after PM2.5 exposure in vivo and in vitro. Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…These cytoplasmic vacuoles might indicate the formation of numerous autophagic vacuoles as an adaptive response to the repeated exposure to DEP. This notion could be further confirmed by ultrastructural evaluation of the renal tubules (an issue that has not been addressed herein) as demonstrated by Huang et al 13 who displayed the formation of autophagosomes in electron microscopic studies of renal tubules of particulate matter (PM2.5)-exposed rats rather than filtered airexposed animals.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These cytoplasmic vacuoles might indicate the formation of numerous autophagic vacuoles as an adaptive response to the repeated exposure to DEP. This notion could be further confirmed by ultrastructural evaluation of the renal tubules (an issue that has not been addressed herein) as demonstrated by Huang et al 13 who displayed the formation of autophagosomes in electron microscopic studies of renal tubules of particulate matter (PM2.5)-exposed rats rather than filtered airexposed animals.…”
Section: Discussionsupporting
confidence: 63%
“…11 On the other hand, exaggerated levels of autophagy can initiate cell death, as well. 12 Hence, Huang et al 13 reported a nephrotoxic effect of airborne particulate matter (PM2.5) via activation of the autophagy pathway.…”
mentioning
confidence: 99%
“…PM2.5 exposure activates the autophagy markers in the spleen of SD rats, such as ATG5, VSP34, Beclin 1, and LC3 [ 174 ]. PM2.5 exposure induces renal injury and changes autophagy markers, such as p62, Beclin 1, and LC3, in rats and HK-2 cells [ 175 ]. Diesel exhaust particles (DEP) induce the generation of ROS, pro-inflammation, and apoptosis in the HUVEC tube cells [ 176 ].…”
Section: Autophagy-related Responses To Mss and Nss In Animal And Cell Linesmentioning
confidence: 99%